LONG-TERM EFFECTS OF A MULTIDISCIPLINARY OPTIMISATION PROGRAM IN A CANCER POPULATION - Jamie Young; Annie Lu; Rachel Slattery; Celia Marston; Marnie Fitzgerald; Anna Beaumont; Oliver Holmes (Journal of Cancer Rehabilitation, 2023)
Background/Aims The ‘Optimisation Clinic’ is a multidisciplinary program designed to optimise physical function, nutritional status, fatigue and quality of life prior to, during and after cancer treatment. There is a paucity of evidence on the efficacy of multidisciplinary cancer programs and the aims of this study are to investigate the long-term impact of a multidisciplinary program and to discuss the challenges with implementation of the Optimisation Clinic. This study will also investigate the prevalence of cancer-related pain in this cohort. Methods This study was a retrospective audit and a prospective cohort study. Participants were recruited from a list of patients who had attended the Optimisation Clinic and phone calls for follow-up were at least 3 months post intervention. Outcome measures included the Australian Modified Karnofsky Score, Brief Fatigue Inventory, International Physical Activity Questionnaire, Patient Health Questionnaire 4 and the Patient-Generated Subjective Global Assessment. In addition, questions about cancer-related pain including the presence of cancer pain, its duration, location and impact were asked. Results There was a total of 83 participants who attended the Optimisation Clinic and a majority of the participants were diagnosed with lung cancer. At follow-up, 21 participants were contacted by phone. Post completion of the Optimisation Clinic program, there was a similar percentage of participants who still required occasional assistance and less people were inactive. There were 40% of participants who were assessed as well nourished. On follow-up the majority of participants were able to perform activities with minor effort, fatigue had also improved and inactivity was reduced at follow-up. Conclusions This study also shows that there are improvements in physical activity, nutritional status, self-care and fatigue management, up to at least 3 months post program completion. In addition, chronic pain was found to be prevalent in this cohort and should therefore be considered in all cancer participants.